2015
DOI: 10.1103/physrevb.91.035107
|View full text |Cite
|
Sign up to set email alerts
|

Improved ground-state electronic structure and optical dielectric constants with a semilocal exchange functional

Abstract: A recently published generalized gradient approximation functional within density functional theory (DFT) has shown, in a few paradigm tests, an improved KS orbital description over standard (semi)local approximations. The characteristic feature of this functional is an enhancement factor that diverges like s ln(s) for large reduced density gradients s which leads to unusual properties. We explore the improved orbital description of this functional more thoroughly by computing the electronic band structure, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 105 publications
2
22
0
Order By: Relevance
“…Thus, both realigned versions of the AK13 and the BJ potential mimic a feature associated with the derivative discontinuity (DD) [16] of the exact exchange (EXX) functional. Moreover, both models for exchange share additional attractive properties such as a step structure in the potential for well-separated subsystems and an improved shell structure in the potential for atoms [36,55]; in bulk systems, they show band gaps, band structures, and optical dielectric constants closer to EXX results [50,55,60]and are thus typically in better agreement with experiments. Hence, AK13 and BJ functionals implement several promising features.…”
Section: Ak13 and Bj Model Reviewmentioning
confidence: 90%
“…Thus, both realigned versions of the AK13 and the BJ potential mimic a feature associated with the derivative discontinuity (DD) [16] of the exact exchange (EXX) functional. Moreover, both models for exchange share additional attractive properties such as a step structure in the potential for well-separated subsystems and an improved shell structure in the potential for atoms [36,55]; in bulk systems, they show band gaps, band structures, and optical dielectric constants closer to EXX results [50,55,60]and are thus typically in better agreement with experiments. Hence, AK13 and BJ functionals implement several promising features.…”
Section: Ak13 and Bj Model Reviewmentioning
confidence: 90%
“…28,36,66,67 In addition to these potentials, we consider in this work the BJ potential 22 which is of stray type (see Refs. 32 and 37) and has the form…”
Section: Talman and Shadwickmentioning
confidence: 99%
“…Experimental values of the fundamental gaps are from Refs. [11,29]. We emphasize that one cannot make a direct quantitative comparison between KS band gaps and experimental gaps.…”
Section: Results On Atomic Energies and The Energetics Of Solidsmentioning
confidence: 96%
“…Compared to the local-density approximation (LDA), and the widely used generalized-gradient approximation (GGA) functional of Perdew, Burke, and Ernzerhof [10] (PBE), it improves on the electronic structure and optical dielectric constants [11], which indicates that its KS orbitals resemble more the true quasiparticle electron states of the system. For atoms and small molecules, Cerceira et al found an overall improvement of the first ionization potential as obtained from the highest occupied KS eigenvalue [12].…”
Section: Introductionmentioning
confidence: 99%